PEMBERDAYAAN KELOMPOK PKK DESA PULUTAN WETANKECAMATAN WURYANTORO KABUPATEN WONOGIRIMELALUI INTRODUKSI TEKNOLOGI PENGOLAHANKLOBOT JAGUNG - dan I.F.Bambang Sulistyono, Emi Widiyanti, Yayan Suherlan, (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2013)
AbstrakActivity in this program are to disseminate the use of cornhusk, totrain suvenir creation of cornhusk, to develop entrepreneurial motivation(Business Motivation Training), and to accompany in marketing andpioneered the establishment of a new business group.This event was attended by 30 participants PKK members PulutanWetan Village. The skill set include: preparation techniques cornhuskingredients, how to cultivate cornhusk become flowers for the table, flowersto decorate the tissue, making brooches and ornaments for the hairpin.In the process of mentoring has formed two new business groupsnamely "Mawar" and "Melati". To the accompaniment of marketing, hasestablished partnerships with local saler flowers in Solo. The results indicatethat the evaluation of the activities of the quality of the products and theirdesign is still lacking. Besides business groups that have been formed yetpowerful and yet function optimally by members. For it is expected therewill be ongoing activities aimed at improving product design, finishingtechniques, marketing management and institutional strengthening of thebusiness group has been formed.